Evaluation of scientific outputs of Kashan University in Scopus Citation Database 2012-2016 - Fatemeh Abbasi Niasar; Saeid Ghaffari (مجله علم‌سنجی کاسپین, 2017)
Background and aim: Scientometrics is a modern field of library and information science, which is used to measure the sciences quantitatively at national and international levels in order to rank the publications, universities and countries. The aim of this study was to determine the scientific outputs of faculty members in Kashan University as a sample of Iranian universities from 2012 to 2016. Material and methods: Data were collected from Scopus through scientometric method. Scientific outputs of faculty members in Kashan University were evaluated from 2012 to 2016. Data were analyzed using Excel and SPSS 20 via ANOVA and T-student tests. Findings: Results showed that the highest number of scientific outputs was original articles (89.3%) of which 85.49% were written by male researchers. Faculty members with degree of professor had the highest number of scientific outputs (41.2%). There was no significant relationship among different educational groups in terms of scientific outputs (P=0.31). Faculty members of the basic sciences (59.55%) and engineering (36.59%) had the highest scientific outputs, respectively. Conclusion: The results indicated that scientific outputs of this University have been had ascending trend during recent five years, which is an effective factor in improving and promoting the scientific status of Kashan University among national and international universities.